RENAL SYMPATHETIC AND SENSORY NERVES DO NOT DRIVE HYPERTENSION IN A POLYCYSTIC KIDNEY DISEASE RAT MODEL. (June 2018) - Li, Sheran; Hildreth, C.M.; Rahman, A.A.; Tallapragada, V.J.; Phillips, J.K.
Abstract : Objective: Catheter-based renal denervation (RDN) is used to treat hypertension however recent clinical trials have cast doubt on previously reported effects. This study aims to determine if RDN improves systolic blood pressure, renal function and autonomic dysfunction in a hypertensive rodent model due to polycystic kidney disease (PKD). Figure. No caption available. Design and method: Lewis polycystic kidney rats (LPK) underwent total, selective sensory or sham RDN by periaxonal application of phenol, capsaicin or normal saline, respectively, at 6-weeks-old. Animals then underwent 1) euthanasia at 7-weeks-old, 10-weeks-old or 14-weeks-old or 2) repeat procedure at 10-weeks-old and euthanasia at 14-weeks-old. Blood pressure was measured by radiotelemetry and treatment efficacy determined using renal immunohistochemistry for sensory [calcitonin gene-related peptide [(CGRP)] and sympathetic nerve [tyrosine hydroxylase (TH)] markers. Renal function was determined by plasma creatinine and urea. Autonomic function was assessed using baroreflex sensitivity (BRS at low frequency, αLF and high frequency, αHF). Results: Cortical TH labelling was significantly depleted at 1-week, but returned to ∼23% and ∼32% of control levels by 4-week and 8-week post-total RDN respectively. Pelvic CGRP labelling was largely abolished by 1-week, but returned to ∼43% and ∼80% of control levels by 4-week and 8-week post-total RDN, and to 67% and 97% by 4-week and 8-week post-sensory RDN. Neither total RDN nor sensory RDN reduced SBP in the LPK rats (total vs. sensory vs. sham, 202 ± 22 vs. 213 ± 7 vs. 205 ± 12 mmHg, P = 0.5) between 7–10 weeks. Repeat total RDN did not have any additional impact on SBP compared to a single procedure or shams between 11–14 weeks (P = 0.48). Neither total nor sensory RDN affected αLF (total vs. sensory vs. sham, 1.1 ± 0.1 vs. 1.1 ± 0.0 vs. 1.2 ± 0.0 ms/mmHg, P = 0.6) or αHF (total vs. sensory vs. sham, 2.2 ± 0.2 vs. 1.8 ± 0.1 vs. 2.1 ± 0.1 ms/mmHg, P = 0.1) between 7–10 weeks. Between 11–14 weeks, there was no significant difference in BRS between all groups. Neither procedure worsened plasma creatinine or urea. Conclusions: We conclude that renal sympathetic and sensory nerves do not drive hypertension or autonomic dysfunction in the LPK model of PKD. Furthermore, PKD patients as a cohort might not benefit from the RDN procedure.